Growth and Physical Development of Children at SDN 1 Naikoten Kupang City: Pertumbuhan Dan Perkembangan Fisik Anak Di SDN 1 Naikoten Kota Kupang - Tajuddin, Al Ihzan (Cahaya Ilmu Bangsa Institute, 2024)
Physical education in elementary schools plays a large role in the growth and development of children. Therefore, an educator must know the level of ability of his students to be able to provide material that maximizes the growth of his students. the research conducted by the researcher was a quantitative descriptive study with a sample of SD Naikoten 1 Kota Kupang students. In this study, the researchers limited it to grade 2 students at SD Naikoten 1 Kota Kupang, whose average age was 8 years. The growth and development of boys from 2nd grade to 1st grade in the city of Kupang is still below average.